Trend Akses Lingkungan dan Keluarga dalam Pembentukan Budaya Baca Siswa SD Di Kecamatan Sukamulia - Diana Aswari; Khirjan Nahdi; Zulfadli Hamdi (Jurnal Diferensiasi: Jurnal Hasil Penelitian, Pengembangan dan Kajian Kepustakaan di Bidang Pendidikan, 2026)
Abstract: This study aims to (1) analyze the influence of environmental access on the formation of a reading culture among elementary school students in Sukamulia District, (2) assess the role of the family in supporting the formation of a reading culture among elementary school students in Sukamulia District, (3) identify obstacles faced in forming a reading culture among elementary school students in Sukamulia District. This study uses a qualitative approach with a descriptive method. The research subjects include elementary school students and parents. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. Data validity was obtained through triangulation, increased persistence, and member checks. The results of the study indicate that environmental access to students' reading culture is still limited, indicated by a lack of reading materials at home, suboptimal literacy facilities at school, and low community support. The role of families, especially parents, is not optimal due to low levels of education, limited time, and economic conditions, so they are unable to be effective role models or companions for their children. Other obstacles found include low student reading motivation, the dominant use of digital media for entertainment, and a lack of synergy between schools, families, and the community. Thus, developing a reading culture among elementary school students in Sukamulia District requires a collaborative strategy through the provision of interesting reading materials, active family involvement, strengthening school literacy programs, and developing community-based literacy communities. Abstrak: Penelitian ini bertujuan untuk(1) menganalisis pengaruh akses lingkungan terhadap pembentukan budaya baca siswa SD di Kecamatan Sukamulia, (2) menilai peran keluarga dalam mendukung pembentukan budaya baca pada siswa SD di Kecamatan Sukamulia, (3) mengidentifikasi hambatan-hambatan yang dihadapi dalam membentuk budaya baca di kalangan siswa SD di Kecamatan Sukamulia. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Subjek penelitian meliputi siswa sekolah dasar dan orang tua Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diperoleh melalui triangulasi, peningkatan ketekunan, dan member check. Hasil penelitian menunjukkan bahwa akses lingkungan terhadap budaya baca siswa masih terbatas, ditandai dengan minimnya bahan bacaan di rumah, kurang optimalnya fasilitas literasi di sekolah, serta rendahnya dukungan masyarakat. Peran keluarga, khususnya orang tua, belum maksimal akibat rendahnya tingkat pendidikan, keterbatasan waktu, serta kondisi ekonomi, sehingga belum mampu menjadi teladan maupun pendamping efektif bagi anak. Hambatan lain yang ditemukan meliputi rendahnya motivasi membaca siswa, dominasi penggunaan media digital untuk hiburan, serta kurangnya sinergi antara sekolah, keluarga, dan masyarakat. Dengan demikian, pembentukan budaya baca siswa SD di Kecamatan Sukamulia memerlukan strategi kolaboratif melalui penyediaan bahan bacaan yang menarik, pelibatan aktif keluarga, penguatan program literasi sekolah, dan pengembangan komunitas literasi berbasis masyarakat.